2020
DOI: 10.35842/formil.v5i1.299
|View full text |Cite
|
Sign up to set email alerts
|

hubungan dukungan keluarga dan kepatuhan minum obat terhadap kesembuhan penderita tuberkulosis (tb) di kabupaten bantul

Abstract: latar belakang: world health organization (who) 2017 diperkirakan kasus 1.020.000 kasus tuberkulosis di indonesia. masalah pada penderita tb adalah ketidak patuhan penderita tb paru. tujuan penelitian untuk mengetahui hubungan dukungan keluarga dan kepatuhan minum obat terhadap kesembuhan penderita tuberkulosis (tb) di kabupaten bantul.metode penelitian: metode penelitian dengan rancangan cross-sectional. pengampilan sampel dilakukan dengan proposive sampling dengan jumlah sampel 39 penderita. analisis data di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 1 publication
(1 reference statement)
0
2
0
3
Order By: Relevance
“…It showed that the high frequency of socio-emotional communication is related to patients' high adherence not to stop drug consumption rules. This phenomenon has been highlighted by two previous papers, [19] and [20] which states that everyone needs the support of empathy and sympathy love, trust, and respect. The pharmacist and the patients' concern can alleviate the problems and even help solve the problems faced.…”
Section: Resultsmentioning
confidence: 90%
“…It showed that the high frequency of socio-emotional communication is related to patients' high adherence not to stop drug consumption rules. This phenomenon has been highlighted by two previous papers, [19] and [20] which states that everyone needs the support of empathy and sympathy love, trust, and respect. The pharmacist and the patients' concern can alleviate the problems and even help solve the problems faced.…”
Section: Resultsmentioning
confidence: 90%
“…The previous study 17 showed that droplet were the main focus of mode of transmission for both disease. The reduction strategy of COVID-19 in the previous study was offered through herbal intervention.…”
Section: Discussionmentioning
confidence: 94%
“…Dukungan informasi, penghargaan, instrumental, dan emosional dari keluarga memiliki hubungan erat terhadap kepatuhan minum obat (21). Tingkat pengetahuan seseorang yang baik mengenai TB, kemauan dan keyakinan penderita TB untuk sembuh dapat mempengaruhi perilaku pasien terhadap kepatuhan menjalani pengobatan minimal selama 6 bulan (7).…”
Section: Metodeunclassified